2017
DOI: 10.1210/jc.2017-00627
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Tumor Suppression by Combination of Cabergoline and Chloroquine

Abstract: The data suggest that combined use of CAB and CQ may increase clinical effectiveness in treatment of human pituitary adenomas, as well as other cancers, making it an attractive option in tumor and cancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 39 publications
3
15
0
1
Order By: Relevance
“…If patients are resistant or intolerant to one DA, a switch to another DA is recommended. Recently, Lin et al [23] reported that the combination of cabergoline and chloroquine may also be an alternative treatment option. Surgery is associated with a higher risk of morbidity due to possible complications of hypopituitarism and should be offered to patients who do not respond to different DA, even in high doses.…”
Section: Discussionmentioning
confidence: 99%
“…If patients are resistant or intolerant to one DA, a switch to another DA is recommended. Recently, Lin et al [23] reported that the combination of cabergoline and chloroquine may also be an alternative treatment option. Surgery is associated with a higher risk of morbidity due to possible complications of hypopituitarism and should be offered to patients who do not respond to different DA, even in high doses.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot (WB) assays was performed as previously described ( 30 ). Briefly, we prepared cell extracts for Western blotting in RIPA buffer.…”
Section: Methodsmentioning
confidence: 99%
“…A single study showed that chloroquine, an old drug used in malaria treatment, enhanced cabergoline-induced autophagy and apoptosis in prolactinoma cells in vitro [113]. The same paper also investigated two animal models in which chloroquine increased tumor suppression, allowing cabergoline to exert its effects at a lower dose.…”
Section: Other Pharmacologic Agentsmentioning
confidence: 99%